Deletion of Oncomodulin Gives Rise to Early Progressive Cochlear Dysfunction in C57 and CBA Mice - Climer, Leslie K.; Hornak, Aubrey J.; Murtha, Kaitlin; Yang, Yang; Cox, Andrew M.; Simpson, Preston L.; Le, Andy; Simmons, Dwayne D. (Frontiers in Aging Neuroscience, 2021)
Ca2+ signaling is a major contributor to sensory hair cell function in the cochlea. Oncomodulin (OCM) is a Ca2+ binding protein preferentially expressed in outer hair cells of the cochlea and few other specialized cell types. Here, we expand on our previous reports and show that OCM delays hearing loss in mice of two different genetic backgrounds: CBA/CaJ and C57Bl/6J. In both backgrounds, genetic disruption of Ocm leads to early progressive hearing loss as measured by auditory brainstem response (ABR) and distortion product otoacoustic emission (DPOAE). In both strains, loss of Ocm reduced hearing across lifetime (hearing span) by more than 50% relative to wild type (WT). Even though the two WT strains have very different hearing spans, OCM plays a considerable and similar role within their genetic environment to regulate hearing function. The accelerated ARHL of the Ocm KO illustrates the importance of Ca2+ signaling in maintaining hearing health. Manipulation of OCM and Ca2+ signaling may reveal important clues to the systems of function/dysfunction that lead to ARHL.